2007
DOI: 10.1007/s00420-007-0225-9
|View full text |Cite
|
Sign up to set email alerts
|

A follow up study of vascular disorders in vibration-exposed forestry workers

Abstract: The findings of this follow up study suggest that forestry workers with work experience limited to AV chain saws are still at risk of developing VWF. Cessation of vibration exposure in the retired workers was associated with a beneficial effect on the cold response of digital arteries. Cold-induced digital arterial hyperresponsiveness at the initial investigation was a predictive factor for the onset of VWF over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 12 publications
0
13
0
3
Order By: Relevance
“…A follow-up study (n=128) investigated the occurrence of VWF and the cold response of digital arteries in a group of forestry workers using antivibratory tools. The study showed that VWF is still prevalent among forest workers despite anti-vibration tools, but the cessation of vibration exposure in the retired workers was associated with a beneficial effect on the cold response of digital arteries 81) . Another study examining the effects of cessation of the use of pneumatic tools in shipyard metal workers (n=204) showed that the recovery of skin temperature after a cold challenge in subjects with VWF remained reduced in the symptomatic subjects several years after exposure removal 82) .…”
Section: Peripheral Circulation and Cold Workmentioning
confidence: 86%
“…A follow-up study (n=128) investigated the occurrence of VWF and the cold response of digital arteries in a group of forestry workers using antivibratory tools. The study showed that VWF is still prevalent among forest workers despite anti-vibration tools, but the cessation of vibration exposure in the retired workers was associated with a beneficial effect on the cold response of digital arteries 81) . Another study examining the effects of cessation of the use of pneumatic tools in shipyard metal workers (n=204) showed that the recovery of skin temperature after a cold challenge in subjects with VWF remained reduced in the symptomatic subjects several years after exposure removal 82) .…”
Section: Peripheral Circulation and Cold Workmentioning
confidence: 86%
“…Production was estimated at almost 150 m 3 based on the number of harvested trees during the study (31) and the average tree volume. Tree felling and processing of the 31 observed trees supposed a fuel mixture consumption of 4.350 l (0.029 L·m −3 ) and a lubricant consumption of 1.480 l (0.010 L·m −3 ), indicating a rather low amount of fuels consumed in operations.…”
Section: Time Fuel Lubricant Consumption and Productive Performancmentioning
confidence: 99%
“…We did not find an association between symptoms that could be consistent with HAVS and use of a chain saw in the previous 8 weeks. Nevertheless, vibration exposure has been associated with the development of musculoskeletal disorders among chain saw operators [Bovenzi 2008;Sutinen et al 2006]. The average frequency-weighted chain saw acceleration measurements in these evaluations (8.4 m/s 2 ) is at the upper end of the range (5.9-8.8 m/s 2 ) reported for common chain saws on the European Union market [Griffin et al 2006].…”
Section: Hand-transmitted Vibrationmentioning
confidence: 99%
“…These saws have been reported to exhibit frequency-weighted accelerations in the range of 1.8-2.2 m/s 2 [Sutinen et al 2006]. However, even operators using these modern, AV chain saw models can still exhibit VWF prevalence rates of more than 10% after just a few years of forestry work [Bovenzi 2008;Sutinen et al 2006]. This suggests that there are no completely safe levels of chain saw vibration exposure; chain saw vibration exposures should be limited to the lowest possible levels.…”
Section: Hand-transmitted Vibrationmentioning
confidence: 99%
See 1 more Smart Citation